Flood Management Study in The Upper Kuncir River: Hydrological Analysis and Watershed Conservation - Purboseno, Sentot; Suparto, Suparto; Bujono, Purwo (Journal of Applied Science, Engineering, Technology, and Education, 2024)
Flooding in the Upper Kuncir River, Nganjuk Regency, is an annual issue causing environmental degradation, infrastructure damage, and economic losses. Increased runoff, erosion, and sedimentation have worsened flood risks due to deforestation and land-use changes. This study analyzes flood factors and conservation strategies through hydrological modeling (HEC-RAS), GIS-based erosion analysis, and watershed simulations. Findings show that high soil erosion (50-80 tons/ha/year) and sediment inflow (18,500 m³ annually) have reduced river capacity by 15%. Peak discharge for a 25-year return period is 125.905 m³/s, exceeding the river’s 85.4 m³/s capacity. Check dams, reforestation, and river normalization are proposed to reduce runoff and control sedimentation. Simulations indicate that structural (check dams, river widening) and non-structural (vegetative cover, soil conservation) measures can reduce peak discharge by 50%. Adaptive reservoir operations at Margopatut Dam can enhance flood control. Integrated watershed management combining engineering and ecohydrological solutions is recommended to ensure sustainable flood mitigation